A Case of Adolescent Cronkhite-Canada Syndrome - Gouvea Faria, Mikaell Alexandre; Basaglia, Bruna; Moutinho Nogueira, Vinicius Quintiliano; Gama Ferraz de Mendonca, Tatiana Barros; Kaiser Junior, Roberto Luiz; Zotarelli Filho, Idiberto Jose [UNESP]; Quadros, Luiz Gustavo de (Elmer Press Inc, 2018)
The Cronkhite-Canada syndrome (CCS) was first reported in 1955, since then more than 500 cases have been reported, indicating an estimated incidence of one case per 1 million inhabitants. The syndrome occurs predominantly in male, with a ratio of three males to two females. Because of the rarity of the syndrome, there are no evidence-based therapies and the treatments described include a combination of therapies, but none is consistently effective. Surgery is usually reserved for the treatment of complications. Herein, we present a case of adolescent CCS. The patient was a 15-year-old boy who presented with watery diarrhea with 20 episodes a day, vomiting and abdominal pain for 4 weeks, with a weight loss of 8.0 kg (15.0% of initial weight). Endoscopic examination revealed polyposis in the stomach, duodenum, and colon. CCS was diagnosed and the patient was treated with a combined corticosteroid and metronidazole. Followed up at 8 month after the diagnosis, the patient was asymptomatic.
Keywords: Cronkhite-Canada syndrome; Symptoms; Treatment; Rare case